Interfirm networks theory, strategy, and behavior - Baxter, Roger, 1944-; Woodside, Arch G. (Bingley, U.K. : Emerald, 2011)
Nearly all business-to-business firms interact and have contractual relationships with upstream, downstream and parallel operating enterprises. How firms design and implement these relationships effectively, overcome poorly performing network linkages, and manage change in interfirm networks are the major topics that Volume 17 covers. The five papers in Volume 17 report new theory and in-depth descriptions of interfirm network behavior. Each paper includes extensive reviews of the relevant literature on interfirm network behavior as well as data analysis using empirical positivistic and/or case study research methods.More than 150 figures and tables support the discussion of findings.
Customer value : theory, research, and practice / Arch G. Woodside, Francesca Golfetto, Michael Gibbert -- Intangible value in buyerseller relationships / Roger Baxter -- Final customers value in business networks / Stephan C. Henneberg, Stefanos Mouzas -- Functions, trust, and value in business relationships / Thomas Ritter, Achim Walter -- Customer value metrics / Bruno Busacca, Michele Costabile, Fabio Ancarani -- Total cost of ownership and customer value in business markets / Gabriela Herrera Piscopo, Wesley Johnston, Dan N. Bellenger -- Linking customer value to customer share in business relationships / Wolfgang Ulaga, Andreas Eggert -- Configurations and control of resource interfaces in industrial networks / Enrico Baraldi, Torkel Str$1'Xl(Bsten -- Creating superior value through network offerings / Bernard Cova, Robert Salle -- Competence-based value framing for business-to-business customers / Francesca Golfetto, Fabrizio Zerbini, Michael Gibbert -- Value delivery and value-based pricing in industrial markets / Andreas Hinterhuber -- Value creation options for contract manufacturers : market strategy transition and coevolution in networks / Paul Matthyssens, Koen Vandenbempt, Sara Weyns -- Sensemaking in networks : using network pictures to understand network dynamics / Morten H. Abrahamsen -- SMEs' networking capability and international performance / Breda Kenny, John Fahy -- Managing industrialization : a resource interaction perspective / Tommy Tsung Ying Shih.s
Mode of access: World Wide Web.
Keywords: Business networks